Visual Acuity and Contrast Sensitivity in Preterm and Full-Term Children Using a Novel Digital Test - María Teresa Pérez Roche; Jason C. Yam; Hu Liu; Diego Gutierrez; Chau Pham; Victoria Balasanyan; Gerardo García; Mauricio Cedillo Ley; Sandra de Fernando; Marta Ortín; Victoria Pueyo; on behalf of the TrackAI Research Consortium (MDPI AG, 2022)
Visual assessment in preverbal children mostly relies on the preferential looking paradigm. It requires an experienced observer to interpret the child's responses to a stimulus. DIVE (Device for an Integral Visual Examination) is a digital tool with an integrated eye tracker (ET) that lifts this requirement and automatizes this process. The aim of our study was to assess the development of two visual functions, visual acuity (VA) and contrast sensitivity (CS), with DIVE, in a large sample of children from 6 months to 14 years (y) of age, and to compare the results of preterm and full-term children. Participants were recruited in clinical settings from five countries. There were 2208 children tested, 609 of them were born preterm. Both VA and CS improved throughout childhood, with the maximum increase during the first 5 years of age. Gestational age, refractive error and age had an impact on VA results, while CS values were only influenced by age. With this study we report normative reference outcomes for VA and CS throughout childhood and validate the DIVE tests as a useful tool to measure basic visual functions in children.